HUNIAN AWAL SEJARAH DI PESISIR KAIMANA, PAPUA BARAT (Early History of Setlement in Kaimana Coast, West Papua) - Mahmud, M. Irfan (BALAI ARKEOLOGI PAPUA, 2014)
Coastal Kaimana be one important area to understand overview of the early history of civilization in New Guinea. Kaimana evolved since the empire archipelago use as a transit port as archaeological traces were found. A necessity, residential visited various ethnic groups in the past will also produce a diversity of artifacts. Instead, it is important to know two things from Kaimana coastal sites, namely: (i) the diversity of artifacts; and (ii) the character of the culture that developed in the residential area. Picture of two things is intended to show on the one hand, the contribution of the archipelago to the development of local communities in Papua early history, while on the other hand know the influence of external elements of the character of the local culture. By using a method known archaeological survey that multiculturalism has grown in residential site at Kaimana coast, where the infrastructure reflects the character of the maritime civilization open, advanced, and adaptive to the elements of the outer cover all aspects of life: social, economic, cultural, historical, to religion.ABSTRAKPesisir Kaimana menjadi salah satu kawasan penting untuk memahami gambaran peradaban masa awal sejarah di Pulau Papua. Kaimana berkembang sejak imperium Nusantara menggunakan sebagai pelabuhan transit sebagaimana jejak arkeologi yang ditemukan. Suatu keniscayaan, hunian yang dikunjungi berbagai etnis di masa lalu juga akan menghasilkan keragaman artefak. Justru itu, penting untuk mengetahui dua hal dari situs pesisir Kaimana, yaitu: (i) keragaman artefak; dan (ii) karakter budaya yang berkembang di dalam kawasan hunian. Gambaran dua hal tersebut ditujukan untuk memperlihatkan pada satu pihak kontribusi Nusantara terhadap perkembangan komunitas lokal Papua masa awal sejarah, sementara dilain pihak mengatahui pengaruh anasir luar terhadap karakter budaya setempat. Dengan menggunakan metode survei arkeologi diketahui bahwa multikulturalisme telah berkembang pada situs hunian di pesisir Kaimana, dimana infrastrukturnya mencerminkan karakter peradaban maritim yang terbuka, maju, dan adaptif dengan anasir dari luar melingkupi segala aspek kehidupan: sosial, ekonomi, budaya, sejarah, hingga religi.